Influence of spirituality on the life of people with intestinal stomas: an integrative review (Research, Society and Development, 2022)
People with intestinal stomas face difficulties in adaptation. This study seeks to analyze the scientific evidence regarding the influence of spirituality in the life of the person with an intestinal stoma, through an integrative review that used the following databases: Latin American and Caribbean Literature on Health Sciences, Cumulative Index to Nursing and Allied Health Literature, Scopus and the Pubmed portal. The final sample of selected studies was composed of eleven scientific articles, five from Brazil, two from the United States, two from Iran, one from Taiwan, and one from Vojvodina, seven quantitative, two mixed, and two qualitative. The following guiding question was used: What is the evidence available in the literature on the influence of spirituality in the life of the person with an intestinal stoma? The studies showed that spirituality positively influences the acceptance of the stoma by the person and that health professionals should identify the spiritual needs to help people in this condition.